An Investigation of Aerosol and Ozone Measurements from the Cryogenic Limb Array Etalon Spectrometer: Validation and Relation to Other Chemical Species - Deshler, Terry (1997)
Throughout this study we focused on comparisons of CLAES and in situ measurements of ozone and aerosol extinction. Thus the comparison is between satellite data representative of large spatial regions and in situ data representative of nearly point samples. Both instruments provide vertical profiles, but the region of overlap is limited to between approximately 10 and 100 mb. CLAES Version 7 ozone measurements have been compared to electrochemical cell ozonesonde measurements over McMurdo Station, Antarctica (78 deg S, 167 deg E), Dumont d'Urville, Antarctica (66.7 deg S, 140 deg E), Laramie, Wyoming (41 deg N, 106 deg W), and Bear Island, Norway (74.3 deg N, 19 deg E). Comparisons were made between vertical ozone profiles, and between integrated column ozone over the region of overlap of the measurements. Comparisons using CLAES Version 8 data are underway. CLAES Version 8 aerosol extinction measurements at all wavelengths have also been compared to University of Wyoming aerosol extinctions over McMurdo Station, Antarctica, and over Laramie, Wyoming. Coincidences in all cases were determined by minimizing the distance between the CLAES observations and the surface station, and the time separation between the satellite and in situ measurements.